Coupled‐Waveguides for Dispersion Compensation in Semiconductor Lasers (Laser Photonics Rev. 12(5)/2018). Issue 5 (May 2018) - Bidaux, Yves; Kapsalidis, Filippos; Jouy, Pierre; Beck, Mattias; Faist, Jérôme
Abstract : Semiconductor Lasers In article number1700323, Yves Bidaux and co‐workers present a dual‐waveguide for intracavity dispersion compensation in semiconductor lasers and apply it to a short‐wavelength quantum cascade laser. The fundamental mode of the laser cavity leaks into a second, passive waveguide and creates a new coupled mode. The chromatic dispersion of the coupled mode can be tailored in order to allow for frequency comb operation of the device.